Innovative Pathways in Higher Education: Exploring the Connotation, Characteristics, and Implementation of the "Three Entries" Virtual Teaching and Research Section - Chen Kewei; Yang Aijun (International Journal of Education and Humanities, 2024)
The "Three Entries" virtual teaching and research section is an innovative approach aimed at enhancing the quality of higher education in the new era. By utilizing Xi Jinping: The Governance of China as multilingual teaching materials and leveraging information technology, this initiative promotes collaboration across schools, departments, majors, and time zones. The primary challenge addressed by this study is how to improve educational quality while fostering cross-institutional collaboration. The "Three Entries" approach features a clear goal, precise demonstration, material sharing, and collaborative teaching. Several key methods are employed to implement this approach. First, enhancing the top-level design ensures that the initiative's goals and strategies align with the broader vision of higher education institutions. Second, strengthening the construction of platforms facilitates resource sharing and collaboration among various institutions. Third, enriching the content of teaching materials ensures that they are relevant and of high quality. Fourth, the approach emphasizes a teacher-led, student-oriented learning mode that encourages interactive and collaborative learning. Finally, optimizing the synergistic effects of cross-institutional collaboration is crucial for achieving better educational outcomes. The results of implementing the "Three Entries" virtual teaching and research section have been significant. There has been a notable improvement in the quality of education, with students showing increased engagement and motivation. Additionally, enhanced collaboration across departments and majors has created a more dynamic and interactive learning environment. Based on these findings, several recommendations are proposed to strengthen the initiative further. The essential steps are to continuously improve top-level design, expand and enhance the technology platforms, enrich teaching content, develop more interactive learning methods, and optimize cross-institutional collaboration. This innovative approach effectively addresses the fundamental goal of cultivating well-rounded college students, preparing them for the challenges of the future